N and C-atoms in R (Ar)-\(N_2\)-\(CH_4\) Flowing Afterglows in High Power RF Jet - A. Ricard; S. Cavadias (Plasmas Afterglows with \(N_2\) for Surface Treatments - Edition 3, 2023)
Radiative species in Ar RF plasma torch with addition of H2, CH4 and CF4 polluting gases have been analysed by emission spectroscopy. An efficient etching by F atoms of reactor quartz tube is detected from Si atom emission when a few 10-3 CF4 was introduced into the Ar plasma. The Si emission disappeared with H2 introduction into the Ar - CF4 gas mixture which has been correlated with HF formation. From C atom emission, it is deduced that CF4 as CH4 polluting gases are largely dissociated into the Ar plasma torch. The C-atom density was evaluated from the N-atom density measured by NO titration by considering the part of N+N recombination which populated the N2 (B,v’) radiative states. It is found that the RF 64 MHz plasma jet at 3 kW brought N and C -atoms densities in an afterglow at 3 10-2s near the atmospheric gas pressure which are respectively 1016 cm-3 and 1015 cm-3 are 101 and 102 higher than in 2450 MHz afterglows at about 100 W and 10 Torr.